Metadata and semantic research : 12th International Conference, MTSR 2018, Limassol, Cyprus, October 23-26, 2018, Revised selected papers /: 12th International Conference, MTSR 2018, Limassol, Cyprus, October 23-26, 2018, Revised selected papers. (2019) - Unknown
No abstract available